The SOLARIS observatory: a smart Solar imaging system at high radio frequency for continuous Solar monitoring and space weather applications - Pellizzoni, Alberto; Potenza, Marco; Cavaliere, Francesco; Cuttaia, Francesco; Gervasi, Massimo; Passerini, Andrea; Villa, Fabrizio; Boria, Enea; Bruni, Ivan; Buttu, Marco; De Petris, Marco; Della Torre, Stefano; et al. (Ground-based and Airborne Telescopes X, 2024)
Solaris is a scientific and technological project aimed at the development of a smart Solar monitoring system at high radio frequencies, based on single-dish imaging techniques. It combines the implementation of dedicated and interchangeable high-frequency receivers on existing small single-dish radio telescope systems (1.5/2.6m class) available in our laboratories and in Antarctica, to be adapted for Solar observations. Solaris can perform Solar imaging observations nearly 20h/day during Antarctic summer with optimal sky opacity, and it will be the only Solar facility offering continuous monitoring at 100 GHz. In perspective, our system could be implemented also in the Northern hemisphere to offer unprecedented Solar radio monitoring and imaging for the whole year.